Tumor ósseo multilobular (Condroma rodens) em um cão - Bohrer, Ana Paula Fauth; dos Santos, Franciele Rossi; Sperhacke, Carla Jenifer; Rasador, Francie; Streck, André Felipe; Jaconi, Fernanda Castellarin; Bastian, Natália Carolina; França, Raqueli Teresinha (Acta Scientiae Veterinariae, 2017)
Background: The multilobular tumor of bone, also known as chondroma rodens, is a primary tumor of bones with low frequency in dogs. It is considered a slow-growth malignant tumor, locally invasive, able to compress and invade the cerebral tissue. Its occurrence is greater in the flat bones of skull and hard palate. The clinical signs depend on the tumor location and usually are related to the compression of adjacent structures. The aim of this study is present a multilobular tumor of bone clinical case in a dog with has progressive growth on the skull’s frontal part and facial deformation. Clinical, laboratory and therapeutic findings will be discussed in the report. Case: An 8-year-old male crossbred castrated dog, weighing 31 kg, presenting progressive growth in the skull was examined at the University of Caxias do Sul veterinary clinic. According to the owner, the tumor was firstly observed about 3 months ago, and the dog became prostrated since then. In the clinical examination, was noticed an enlarged, symmetric and diffuse volume in the skull’s frontal part, facial deformation, especially around the ocular region, causing visual deficit. It wasn’t detected any other systemic alterations. The radiography of the skull revealed a soft tissue increased volume, suggesting a mass or an encapsulated abscess. Serum biochemistry demonstrated an increase of alcaline phosphatase activity. The other hematological and biochemical parameters were within normal limits. Fine needle aspiration was performed, showing compatible result with bone neoplasm. It was chosen to make a surgical resection, starting with a cross-shaped incision on medial portion of the skull, followed by a skin disclosure to expose the tumor. With the assistance of an orthopedical chisel and metzembaum scissors, the mass was removed. The tumor presented steady and sanded aspect, reddish colored with whitish areas. Due to the anatomic area and evolved structures, it was not possible to make the total removal of the tumor with a safety margin. Fragments were sent to histopathological examination, and the final diagnosis was multilobular tumor of bone. After hospital discharge, antibiotic cefalexin and analgesia was prescribed tramadol hydrochloride and carprofen. Weekly follow-up and reviews were performed, with points with drawn within 15 days. One month after the surgery, the dog came back to the review feeling prostrated and presenting a new mass (in the same location), causing him once more visual deficit. The owner opted to euthanize, not authorizing necropsy. Discussion: The multilobular tumor of bone is considered a slow-growth malignant tumor that usually occurs on the dog’s skull. The clinical signs are related to the compression of the affected structures. In this case, the animal has visual deficit due to the mass growth above ocular region. The multilobular tumor of bone is considered rare in dogs, however it is important to know this disease manifestations, allowing the best intervention to be done. It is important to emphasize that the cytological findings are similar of those on osteosarcoma, so it is considered as a differential diagnosis. The histopathological examination is indispensable to make the final diagnosis. The surgical resection may provide better quality of life and longer survival and must be evaluated according to each case.